Effects of combined aerobic-resistance training on health-related quality of life and stress in sedentary adults - Silva, Fernanda M.; Ferreira, José P.; Teixeira, Ana M.; Massart, Alain; Duarte-Mendes, Pedro (Frontiers in Aging, 2025)
IntroductionPoor quality of life and psychological stress have been associated with worse clinical outcomes, including anxiety and depression disorders, cardiovascular diseases, metabolic syndrome, type 2 diabetes, and premature mortality. Evidence suggested that physically active adults were more likely to report better quality of life and increased capacity to deal with stress, compared to their sedentary peers. This study examines the effects of 16 weeks of combined aerobic and resistance exercise training on health-related quality of life (HRQoL) and stress levels in sedentary adults.MethodsThis study involved previously sedentary middle-aged workers (n = 36), randomized, and allocated into control (n = 18) and exercise (n = 18) groups. The exercise group performed 16 weeks of combined exercise training for 75 min, three times/week. The HRQoL was assessed using the SF-36 survey and Satisfaction with Life Scale. Stress levels were assessed subjectively using the Perceived Stress Scale and objectively by the salivary cortisol and alpha-amylase concentrations. Intra- and inter-group analysis were performed using a mixed ANOVA or Friedman’s test.ResultsIn relation to SF-36 results, a significant improvement in the mental component summary (p = 0.047, Kendall’s W = 0.170 (small effect)) and social functioning subdomain (p = 0.040, Kendall’s W = 0.179 (small effect)) was found for the exercise group after the intervention. A significant difference between groups was found in mean differences (Δ) in the mental health subdomain, with superiority in the exercise group (exercise group, Δ = 7.50 vs. control group, Δ = −5.00; p = 0.006). After 16 weeks of follow-up, the exercise group perceived reduced stress levels compared to the control group (exercise group, Δ = −3.67 points vs. control group, Δ = 0.94 points; p > 0.05); although not significant, this result is clinically relevant. The exercise program had no significant effect on salivary stress biomarkers.DiscussionThe present study’s findings may have important clinical implications because they show that middle-aged sedentary workers are likely to benefit from adopting a regular combined exercise training regimen to promote better HRQoL (i.e., mental health component) and wellbeing.Clinical Trial Registrationclinicaltrials.gov, identifier NCT04868240.